Desetletja raziskovanj v publikacijah ZRC SAZU - Pokorn, Daša (2018)
The Research Centre of the Slovenian Academy of Sciences and Arts (ZRC SAZU) was established as an independent public research institution in 1981. It provided an institutional structure for a number of institutes that had already existed for several decades, organized as research departments of the Slovenian Academy of Sciences and Arts. After forty years of turbulent, exciting, and successful transformations, ZRC SAZU has become the leading research and educational centre in Slovenia, mainly in the humanities and social sciences, and one of the most prominent academic institutions in central and southeastern Europe. More than three hundred researchers work within eighteen interconnected institutes that create a dynamic transdisciplinary research network. ZRC SAZU publishes around 60 to 90 monographs annually and from 25 to 30 volumes of each title from an array of their science journals. It is an active supporter of open science.Over the last four decades, ZRC SAZU has become one of the driving forces of citizen engagement in science. It offers a forum for discussions of socially relevant issues and holds a series of public events.
Scientific Research Center of the Slovenian\nAcademy of Sciences and Arts (ZRC SAZU) is one of the leading research and\neducational centres in Slovenia, equivalent to prominent academic institutions\nof the Central and South Eastern Europe. It is an independent institution since\n1981, although the majority of its institutes had operated under the auspices\nof the Slovenian Academy of Sciences and Arts. The work of ZRC SAZU is highly\ninterdisciplinary: it is based on cooperation, complementarity and synergy.\nMore than three hundred associates are organized in eighteen independent\ninstitutes, which are coordinated and interconnected. Numerous and different\nfields of research could be summarized in the study of cultural, social and\nnatural phenomena, processes and practices. Results of the work are also\nreflected in scientific, professional and popular articles, in printed\nmonographs, and in online versions.